A Descriptive Study on the Infection Control Practices of Dentists in an Urbanized City in the Philippines During the COVID-19 Pandemic within the Period of General Community Quarantine (September 2020-MArch 2021)/Ma. Bianca B. Barrameda, Ma. Chrizel Ian A. Madlangbayan, and Joshua Marcel A. Sy. - Barrameda, Ma. Bianca B. Author; Madlangbayan, Ma. Chrizel Iana A. Author; Sy, Joshua Marcel A. Author; Karganilla-Frange, Melanie Ruth M. (2023)
Introduction: The global impact of the COVID-19 pandemic has instigated a profound
public health crisis, particularly affecting professionals like dentists who, due to their close
interaction with saliva—a potential viral reservoir—and the aerosols generated during
specific procedures, face elevated risks of infection. To mitigate this, the Centers for Disease
Control and Prevention (CDC) and the Philippine Dental Association (PDA) have
established guidelines deemed imperative for averting cross-infection in dental settings. This
study, conducted in an urbanized Philippine city, delves into the infection control practices
of dentists amid the pandemic.
Methods: An online survey covered participants' demographics, patient triage, engineering,
administrative controls, disinfection, personal hygiene, personal protective equipment (PPE),
and waste management practices. Descriptive statistics, employing frequency distributions
and percentages, summarized the dentists' adherence to infection control protocols.
Results: The findings disclosed variability in dentists' compliance with recommended
guidelines. While a considerable majority (92%) provided their teams orientation on
COVID-19 infection control protocols before reopening, disparities emerged in certain
practices. Notably, 57% deferred elective procedures and 43% postponed aerosol-generating
procedures (AGPs). Furthermore, only 39% utilized rubber dam isolation during AGPs.
Conclusion: Though many dentists demonstrated adherence to patient triage and

administrative controls, discrepancies surfaced in using rubber dams, Rt-PCR tests, and four-
handed dentistry. Additionally, the study identified gaps in employing biodegradable
materials and third-party treatment storage and disposal. Emphasizing the significance of
robust infection control measures, the research underscores their dual role in preventing
cross-infections and fortifying dental teams for potential future challenges.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Infection control, Dental; Covid-19 pandemic